Clinical Impact of Ceftriaxone Resistance in Escherichia coli Bloodstream Infections: A Multicenter Prospective Cohort Study. (27th October 2022) - Tamma, Pranita D; Komarow, Lauren; Ge, Lizhao; Garcia-Diaz, Julia; Herc, Erica S; Doi, Yohei; Arias, Cesar A; Albin, Owen; Saade, Elie; Miller, Loren G; Jacob, Jesse T; Satlin, Michael J; et al.
Abstract: Background: Ceftriaxone-resistant (CRO-R) Escherichia coli bloodstream infections (BSIs) are common. Methods: This is a prospective cohort of patients with E coli BSI at 14 United States hospitals between November 2020 and April 2021. For each patient with a CRO-R E coli BSI enrolled, the next consecutive patient with a ceftriaxone-susceptible (CRO-S) E coli BSI was included. Primary outcome was desirability of outcome ranking (DOOR) at day 30, with 50% probability of worse outcomes in the CRO-R group as the null hypothesis. Inverse probability weighting (IPW) was used to reduce confounding. Results: Notable differences between patients infected with CRO-R and CRO-S E coli BSI included the proportion with Pitt bacteremia score ≥4 (23% vs 15%, P = .079) and the median time to active antibiotic therapy (12 hours [interquartile range IQR, 1–35 hours] vs 1 hour [IQR, 0–6 hours]; P < .001). Unadjusted DOOR analyses indicated a 58% probability (95% confidence interval [CI], 52%–63%) for a worse clinical outcome in CRO-R versus CRO-S BSI. In the IPW-adjusted cohort, no difference was observed (54% [95% CI, 47%–61%]). Secondary outcomes included unadjusted and adjusted differences in the proportion of 30-day mortality between CRO-R and CRO-S BSIs (−5.3% [95% CI, −10.3% to −.4%] and −1.8 [95% CI, −6.7% to 3.2%], respectively), postculture median length of stay (8 days [IQR, 5–13 days] vs 6 days [IQR, 4–9 days]; P < .001), and incident admission to a long-term care facility (22% vs 12%, P = .045). Conclusions: Patients with CRO-R E coli BSI generally have poorer outcomes compared to patients infected with CRO-S E coli BSI, even after adjusting for important confounders.